2016
DOI: 10.1051/0004-6361/201527009
|View full text |Cite
|
Sign up to set email alerts
|

Probing the stellar wind environment of Vela X–1 with MAXI

Abstract: Context. Vela X-1 is one of the best-studied and most luminous accreting X-ray pulsars. The supergiant optical companion produces a strong radiatively driven stellar wind that is accreted onto the neutron star, producing highly variable X-ray emission. A complex phenomenology that is due to both gravitational and radiative effects needs to be taken into account to reproduce orbital spectral variations. Aims. We have investigated the spectral and light curve properties of the X-ray emission from Vela X-1 along … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
(60 reference statements)
1
31
0
3
Order By: Relevance
“…This second model (Model 2) resulted into an equivalently good description of the spectrum and it is worth reporting, since it is also adopted in the literature when investigating spectra from HMXB pulsars (e.g. Malacaria et al 2016). A narrow emission line is present in the time-averaged spectrum at an energy of 6.44 keV (consistent with fluorescent emission from almost neutral iron) and a low equivalent width of 40 eV.…”
Section: Discussionmentioning
confidence: 96%
“…This second model (Model 2) resulted into an equivalently good description of the spectrum and it is worth reporting, since it is also adopted in the literature when investigating spectra from HMXB pulsars (e.g. Malacaria et al 2016). A narrow emission line is present in the time-averaged spectrum at an energy of 6.44 keV (consistent with fluorescent emission from almost neutral iron) and a low equivalent width of 40 eV.…”
Section: Discussionmentioning
confidence: 96%
“…Vela X-1 is a high-mass XRB, which also shows variable emission close to the eclipse due to structure in the wind of the supergiant companion (Sidoli et al 2015). It also shows an occasional secondary dip in the orbital light curve at inferior conjunction, attributed to scattering in an ionised accretion wake (Malacaria et al 2016). These differences show that the different components in the accretion structure give different contributions to the full system when the system parameters are different.…”
Section: Similar Sourcesmentioning
confidence: 99%
“…5. In a systematic study of MAXI data, Malacaria et al (2016) found that ∼15% of all orbital light curves showed a dip around φ orb ∼ 0.5, which was best explained by Thomson scattering in an extended and ionized accretion wake. Third, for late orbital phases (φ orb > 0.6) up to the eclipse ingress, the observed absorbing column densities always remain high, but are still significantly variable by a factor of a few.…”
Section: Variations In the X-ray Absorptionmentioning
confidence: 99%